2019
DOI: 10.1038/s41598-019-45338-1
|View full text |Cite
|
Sign up to set email alerts
|

Substrate mediated nitridation of niobium into superconducting Nb2N thin films for phase slip study

Abstract: Here we report a novel nitridation technique for transforming niobium into hexagonal Nb 2 N which appears to be superconducting below 1K. The nitridation is achieved by high temperature annealing of Nb films grown on Si 3 N 4 /Si (100) substrate under high vacuum. The structural characterization directs the formation of a majority Nb 2 N phase while the morphology shows granular nature of the films. The temperature depe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…The explanation that their films actually possess the γ phase and not the β phase is consistent with their observation of T c = 11.5 K, a value consistent with the T c of γ phase films in this study and those reported by Oya [26]. Finally, Gajar et al reported the growth of mixed phase films of β-Nb 2 N and Nb 4 Nb 5 , which exhibit broad superconducting transitions around 1 K [50].…”
Section: Resultssupporting
confidence: 91%
“…The explanation that their films actually possess the γ phase and not the β phase is consistent with their observation of T c = 11.5 K, a value consistent with the T c of γ phase films in this study and those reported by Oya [26]. Finally, Gajar et al reported the growth of mixed phase films of β-Nb 2 N and Nb 4 Nb 5 , which exhibit broad superconducting transitions around 1 K [50].…”
Section: Resultssupporting
confidence: 91%
“…S5 in SI]. This indicates that the samples are in the 2D limit, where phase fluctuations lead to PSLs 35 and IVCs exhibit resistive steps 20 , 36 , 37 . In Fig.…”
Section: Resultsmentioning
confidence: 89%
“…We demonstrate that by tuning the disorder the superconducting-to-normal state transition in the measured IVCs changes from a single step transition to a transition embedded with multiple steps featuring the formation of PSLs. The tuning of disorder level in TiN films has been achieved by adopting a novel substrate mediated nitridation technique 18 20 , which employs high temperature annealing of Ti/Si 3 N 4 based metal/substrate assembly to prepare majority phase TiN thin films accompanied by TiSi 2 and elemental Si as minority phases 18 . Conventionally, TiN films are grown either by using reactive dc sputtering of Ti in presence of Ar/N 2 gas mixtures 21 26 or by atomic layer deposition 27 , 28 in presence of N 2 gas etc 29 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we have probed the metal-substrate interaction in Ti/Si3N4 assembly with respect to annealing temperature (Ta) which plays an important role as it leads to the decomposition of Si3N4 into elemental N and Si, and simultaneously, it provides thermal energy for the decomposed elements to diffuse inside the metal [20,21]. The Ta has been varied in the range from 650°C to 820°C.…”
Section: Introductionmentioning
confidence: 99%